Morphological Studies and Phylogenetic Analysis Unveil a New Species of Russula Subg. Heterophyllinae (Russulaceae, Russulales) from Pakistan - Muhammad Fiaz; Sana; Muhammad Binyamin Khan; Munazza Kiran; Muhammad Ishaq; Abdul Nasir Khalid; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Russula subg. Heterophyllidiae is both ecologically and economically important. In the present study, a new Russula species, R . pakistanica , is described from Mansehra District, Khyber Pakhtunkhwa Province, Pakistan, based on morphology and molecular phylogenetic analyses of internal transcribed spacer (nrITS) region. Both morphological and phylogenetic analyses consistently confirmed that the species described belongs to Russula subg. Heterophyllidiae subsect. Virescentinae . Russula pakistanica is characterized by a concave, centrally depressed, striated, and light gray to cream yellow pileus; narrowly adnate and pale olive‐gray lamellae; clavate and very light gray to creamy buff stipe with bulbous base; broadly ellipsoid and partially reticulated basidiospores (average 8.5 × 6.6 μm); clavate to fusoid hymenial cystidia with obtuse apices; and the absence of marginal cells and pileocystidia. Phylogenetically, it formed a distinct and well‐supported sister clade to Chinese R . pallidula . The new species’ description, illustrations, phylogenetic analyses results, and comparison with closely related taxa are provided in this article.